2018
DOI: 10.1021/acs.jpcc.8b04668
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polymer Fibers Containing a Liquid Crystal Core: Insights into Semiflexible Confinement

Abstract: Encapsulation of the nematic liquid crystal N-(4-methoxybenzylidene)-4-butylaniline (MBBA) into the core of poly(vinylpyrrolidone) (PVP) microfibers has been accomplished via coaxial electrospinning for the first time. Data from optical microscopy, two-dimensional Raman mapping, differential scanning calorimetry, and dielectric spectroscopy have been employed to gain detailed insights into the confinement effects on MBBA in a semiflexible polymer sheath. The electrospun fiber diameters could be tuned easily by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
0
28
0
1
Order By: Relevance
“…Due to growing interest in wearable technology, there is a need for new functional soft, lightweight, elastic materials that facilitate development of wearable devices [1][2][3][4]. Functional fibers that enable sensing without relying on electrical power are of particular interest [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to growing interest in wearable technology, there is a need for new functional soft, lightweight, elastic materials that facilitate development of wearable devices [1][2][3][4]. Functional fibers that enable sensing without relying on electrical power are of particular interest [2].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystals have been incorporated into the core of core-shell fibers via coaxial electrospinning. Nematic single component N-(4-methoxybenzylidene)-4-butylaniline (MBBA) [3] and multicomponent mixtures [7] were encapsulated within polyvinylpyrrolidone (PVP) based shells. Lagerwall et al demonstrated that non-beaded fiber morphology was required for orientation of the liquid crystal and that confinement within the polymer stabilized the nematic state resulting in an increase in the clearing temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are coaxial electrospun fibers with liquid crystalline cores that may be suitable for applications as flexible sensors. [20][21][22][23][24] Nematic liquid crystals possess long-range orientation order but lack translational order. The constituent molecules are highly geometrically anisotropic and achiral.…”
Section: Introductionmentioning
confidence: 99%
“…Of the available techniques, electrospinning has been arguably the most widely used because of its ability to easily produce nanoscale fibers with a variety of morphologies . Some characteristics of electrospun fibers include a large surface area to volume ratio, changes in the crystalline structure, and superior mechanical performance (e.g., increases in tensile strength or flexibility) …”
Section: Introductionmentioning
confidence: 99%